Analisis Efektivitas Prosedur Audit atas Siklus Kas Berdasarkan Laporan Auditor Eksternal dan Pengungkapan Pengendalian Internal pada Entitas Bisnis - Karmila Karmila; Muh. Rijal; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The cash cycle is the account most vulnerable to errors and fraud, making the effectiveness of cash audit procedures and internal controls crucial in ensuring the reliability of a business entity's financial statements. This study uses a descriptive qualitative approach with document analysis, including external auditor reports and internal control documentation, as well as content analysis techniques to assess audit findings patterns and the effectiveness of cash controls. The results show that audit procedures, including substantive testing, third-party confirmation, compliance testing, and bank reconciliation analysis, are capable of detecting material errors, while good internal controls, including segregation of duties, complete documentation, transaction authorization, and routine reconciliation, reduce the frequency of significant audit findings. The relationship between audit procedures and internal controls together improves the accuracy and credibility of financial statements. In conclusion, optimizing audit procedures and strengthening internal cash controls are important for improving the quality of financial statements, mitigating the risk of misstatement, and strengthening corporate transparency and accountability.